2012
DOI: 10.1111/j.1756-1051.2012.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and similarity in the Barbarea vulgaris complex (Brassicaceae)

Abstract: Two subspecies of Barbarea vulgaris are taxonomically recognized as ssp. vulgaris and ssp. arcuata. In addition, two types of Barbarea vulgaris ssp . arcuata occurs in Denmark. Th e G-type is resistant to an herbivorous fl ea beetle ( Phyllotreta nemorum ) whereas the P-type is susceptible. A previous study suggested that the P-type evolved by a loss of resistance from a resistant progenitor. We analyzed the genetic relatedness among eight Barbarea taxa: B. vulgaris spp. vulgaris , B. vulgaris ssp. arcuata G-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Whether the cytochromes P450 involved in saponin biosynthesis of Barbarea species have also specialized is not known. Much later, B. vulgaris differentiated into the G-and P-types, possibly during one of the last ice ages Toneatto et al, 2012). Thus, the two plant types are genetically and geographically differentiated, reproductively somewhat incompatible, and differ for several traits apart from insect resistance and saponin structure (Toneatto et al, 2010;Dalby-Brown et al, 2011).…”
Section: Evolution Of Saponin Biosynthesis In Barbarea Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the cytochromes P450 involved in saponin biosynthesis of Barbarea species have also specialized is not known. Much later, B. vulgaris differentiated into the G-and P-types, possibly during one of the last ice ages Toneatto et al, 2012). Thus, the two plant types are genetically and geographically differentiated, reproductively somewhat incompatible, and differ for several traits apart from insect resistance and saponin structure (Toneatto et al, 2010;Dalby-Brown et al, 2011).…”
Section: Evolution Of Saponin Biosynthesis In Barbarea Speciesmentioning
confidence: 99%
“…It is the only species in this economically important family known to produce saponins. B. vulgaris has further diverged into two separate evolutionary lineages (types; Hauser et al, 2012;Toneatto et al, 2012) that produce different saponins, glucosinolates, and flavonoids (Agerbirk et al, 2003b;Dalby-Brown et al, 2011;Kuzina et al, 2011). Saponins of the one plant type make plants resistant to the yellow-striped flea beetle (Phyllotreta nemorum), diamondback moth (Plutella xylostella), and other important crucifer specialist herbivores (Renwick, 2002); therefore, it has been suggested to utilize such plants as a trap crop to diminish insect damage (Badenes-Perez et al, 2005).…”
mentioning
confidence: 99%
“…arcuata was premature, but that investigation of genetic and chemical diversity in a larger geographic area was needed (Agerbirk et al, 2003). Subsequently, conclusive support for the distinctness of the P-type was obtained from comparison of multiple genetic markers Kuzina et al, 2011;Toneatto et al, 2012) and a partial hybridization barrier between the types was suggested (Toneatto et al, 2010). The Ptype may be identical to var.…”
Section: Introductionmentioning
confidence: 96%
“…The first hypothesis can be eliminated, but differences between chromosomes of the two types were indicated by 'FISH' experiments (Ørgaard and Linde-Laursen, 2008). As the deviating P-type bears no clear resemblance to other tested Barbarea species (Agerbirk et al, 2003;Toneatto et al, 2012), the second hypothesis has no experimental support yet. In contrast, the theory of past allopatric separation has been supported by a recent demonstration of different geographic distributions of the two types: based on the characteristic genetic profiles of the P and G-types, the P-type was found to be widely distributed in Eastern Europe in contrast to a more western distribution of the G-type (Christensen et al, 2014;Hauser et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Plants belonging to the Brassicaceae family exhibit species-specific profiles of glucosinolates, a class of compounds thought to function as a part of a defence mechanism against pathogens and insects (9). Difficulty in establishing evolutionary trends and utilizing morphology in phylogenetic studies has been a challenge due to homoplasy in the family (6,281). The first comprehensive phylogenetic study by Beilstein et al used a sample of 101 genera within the family to assess the chloroplast gene ndhF for an intergeneric relationship (19).…”
Section: Introductionmentioning
confidence: 99%